Community cohesion in the absence of MPA co-design: transforming a paper park in the San Antonio Bay, Argentina - Relano, Veronica; Christodoulou, Sierra; Carbajal, Mirta; Narvarte, Maite (Frontiers in Ocean Sustainability, 2025)
Successful co-design, incorporating different stakeholder perspectives, knowledge and needs is crucial for environmental initiatives, particularly during the Designation Phase of a Marine Protected Area (MPA), where science and local knowledge directly informs policy and governance. As more diverse stakeholders are involved in this phase, more socio-ecological factors are addressed. This contributes to a more objective management plan, accountability and conflict resolution early on, while simultaneously reducing any vested economic or development interests that may sway an MPA's objectives, rules and regulations. The San Antonio Bay MPA, located in Patagonia, Argentina, demonstrated a lack of multi-stakeholder collaboration and ineffective co-design during the MPA's designation phase that led to conflicts rather than solutions. Interviews conducted with locals described the visible socio-ecological consequences including unregulated tourism and unsustainable fishing, which can be often attributed to a lack of community cohesion, empowerment and participation within the MPA. This case study demonstrates how shorebird festivals, a community-led intervention grounded in local culture and livelihoods, can promote intergenerational pro-environmental behavior and stewardship in a “paper park,” i.e., MPAs that are legally designated but ineffective. Through multisector/level partnerships, culturally relevant engagement, the leveraging of media, and bottom-up initiatives, this shorebird festival raises awareness and collective responsibility for the San Antonio Bay MPA and has led to the promotion of other shorebird festivals in Argentina and abroad. Thus, while the festival plays an undeniable and vital role in fostering stewardship and driving positive local change, its full impact in securing the MPA's future is realized when complemented by the state fulfilling its fundamental responsibilities for conservation and addressing pre-existing structural flaws. This must be achieved by enacting local, regional, national and international policies that formalize co-management structures. Such policies could grant community stakeholders a legal and institutionalized role in MPA governance and decision-making, turning paper parks into effective conservation areas that meet the socio-ecological objectives for which they were created.